Ligand Effects in Calcium Catalyzed Ketone Hydroboration - Brand, Steffen; Causero, Andrea; Elsen, Holger; Pahl, Jürgen; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
The first “naked” (Lewis base-free) cationic Ca amidinate complex [tBuAmDIPPCa(C6H6)]+[B(C6F5)4]– was prepared in 62 % yield tBuAmDIPP = tBuC(N–DIPP)2; DIPP = 2,6-diisopropylphenyl by reaction of [tBuAmDIPPCaH]2 with [Ph3C]+[B(C6F5)4]– in chlorobenzene. The ether-free complex tBuAmDIPPCaN(SiMe3)2 was obtained by removal of diethyl ether from its ether adduct. Crystal structures show that the amidinate ligand in both complexes is N,Aryl-chelating. In this coordination mode the bulk of the amidinate ligand is comparable to that of a DIPP-substituted β-diketiminate ligand. Isomers with N,N-coordinating amidinate ligands are circa 15 kcal/mol higher in energy and this coordination mode is only present in case additional ether ligands compensate for energy loss or in case of space limitation at the metal, e.g. in homoleptic (tBuAmDIPP)2Ca. A series of four Ca amidinate complexes, tBuAmDIPPCaX, were tested in the catalytic hydroboration of ketones and aldehydes by pinacolborane (HBpin). Catalytic activities increase for X– = I– < B(C6F5)4 – < (Me3Si)2N– ≈ H–. For catalysts with unreactive anions, like I– or B(C6F5)4 –, catalyst performance increases with the Lewis acidity of the metal and a mechanism is proposed in which HBpin and ketone coordinate to the Ca2+ ion which is followed by direct hydroboration. The more active catalysts with X– = (Me3Si)2N– or H– likely operate through a mechanism which involves intermediate metal hydride (or borate) complexes.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Amidinates; Calcium; Cationic complexes; Homogeneous catalysis; Hydroboration